2013
DOI: 10.1038/npp.2013.176
|View full text |Cite
|
Sign up to set email alerts
|

Subanesthetic Doses of Ketamine Transiently Decrease Serotonin Transporter Activity: A PET Study in Conscious Monkeys

Abstract: Subanesthetic doses of ketamine, an N-methyl-D-aspartic acid (NMDA) antagonist, have a rapid antidepressant effect which lasts for up to 2 weeks. However, the neurobiological mechanism regarding this effect remains unclear. In the present study, the effects of subanesthetic doses of ketamine on serotonergic systems in conscious monkey brain were investigated. Five young monkeys underwent four positron emission tomography measurements with [ 11 C]-3-amino-4-(2-dimethylaminomethyl-phenylsulfanyl)benzonitrile ([ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 79 publications
3
47
0
Order By: Relevance
“…isoflurane, have been shown to decrease cortical extracellular serotonin concentration (Mukaida et al 2007) and to increase [ 3 H]escitalopram binding in rats (Elfving et al 2003). Moreover, in a paradigm more similar to the current study, sub-anaesthetic doses of ketamine have recently been shown to decrease [ 11 C]DASB binding by up to 30 % in NHPs (Yamamoto et al 2013;Yamanaka et al 2014). In the current and previous SERT occupancy studies (Batis et al 2012;Cosgrove et al 2010), ketamine was used to induce anaesthesia and baseline PET measurements may therefore be more affected by ketamine than the post-SSRI measurements.…”
Section: Discussionsupporting
confidence: 68%
“…isoflurane, have been shown to decrease cortical extracellular serotonin concentration (Mukaida et al 2007) and to increase [ 3 H]escitalopram binding in rats (Elfving et al 2003). Moreover, in a paradigm more similar to the current study, sub-anaesthetic doses of ketamine have recently been shown to decrease [ 11 C]DASB binding by up to 30 % in NHPs (Yamamoto et al 2013;Yamanaka et al 2014). In the current and previous SERT occupancy studies (Batis et al 2012;Cosgrove et al 2010), ketamine was used to induce anaesthesia and baseline PET measurements may therefore be more affected by ketamine than the post-SSRI measurements.…”
Section: Discussionsupporting
confidence: 68%
“…This is consistent with a recent work by Shigeyyuki et al, who demonstrated a transient increase of serotonin levels in the extracellular fluid caused by ketamine [47]. The authors concluded that the increase of serotonin level was due to inhibition of SERT since its availability was reduced meanwhile 5-HT 1A receptor was unchanged.…”
Section: Ketaminesupporting
confidence: 92%
“…Some investigators have reported that ketamine affects several neuronal transmission systems, such as dopamine receptor and transporter [43][44][45][46], serotonin receptor and transporter [47], glutamate receptor [48], etc. However, interference of ketamine with VMAT2, another important target in the central nervous system, which mediating monoaminergic transmission, is still unknown.…”
Section: Ketaminementioning
confidence: 99%
“…Indeed, ketamine possesses a rich pharmacology, including activity at sigma receptors (123,124). Moreover, actions within dopaminergic (125)(126)(127) or serotonergic (128)(129)(130)(131)(132) systems have also been postulated as alternate mechanisms for ketamine's antidepressant effects. Conversely, ketamine's unique antidepressant properties may be attributable to distinctions in its pharmacodynamic activity within the NMDA receptor (34,122).…”
Section: Discussionmentioning
confidence: 99%